2014
DOI: 10.1128/jvi.00799-14
|View full text |Cite
|
Sign up to set email alerts
|

N-Myc Interactor Inhibits Prototype Foamy Virus by Sequestering Viral Tas Protein in the Cytoplasm

Abstract: Foamy viruses (FVs) are complex retroviruses that establish lifelong persistent infection without evident pathology. However, the roles of cellular factors in FV latency are poorly understood. This study revealed that N-Myc interactor (Nmi) could inhibit the replication of prototype foamy virus (PFV). Overexpression of Nmi reduced PFV replication, whereas its depletion by small interfering RNA increased PFV replication. The Nmi-mediated impairment of PFV replication resulted from the diminished transactivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…Moreover, unlike hBST2, bBST2A1 displays no inhibitory effect on cell-to-cell transmission of PFV and BFV [90]. Other antiviral proteins include promyelocytic leukemia protein (PML), IFN-induced 35-kDa protein (IFP35), N-Myc interactor (Nmi), and p53-induced RING-H2 protein (Pirh2), which have been recently shown to inhibit FV replication through interacting with Tas [27,[91][92][93]. PML directly interacts with PFV Tas and it interferes with its ability to bind the TREs in the PFV LTR and IP [91].…”
Section: Restriction Factorsmentioning
confidence: 99%
“…Moreover, unlike hBST2, bBST2A1 displays no inhibitory effect on cell-to-cell transmission of PFV and BFV [90]. Other antiviral proteins include promyelocytic leukemia protein (PML), IFN-induced 35-kDa protein (IFP35), N-Myc interactor (Nmi), and p53-induced RING-H2 protein (Pirh2), which have been recently shown to inhibit FV replication through interacting with Tas [27,[91][92][93]. PML directly interacts with PFV Tas and it interferes with its ability to bind the TREs in the PFV LTR and IP [91].…”
Section: Restriction Factorsmentioning
confidence: 99%
“…FV Bet protein has been shown to partially prevent APOBEC action [40][41][42][43]. N-Myc interactor (NMI) as well as a member of the interferon-induced protein (IFP) family, IFP35, can inhibit the replication of the prototype and the bovine FV respectively, by direct interaction with the viral transactivator Tas [46,47]. Tetherin is known to block many different types of enveloped viruses by tethering the budding virus at the cell membrane and is also efficient to prevent FV release [48,49].…”
Section: Sfv Genetic Stabilitymentioning
confidence: 99%
“…NMI is elevated rapidly in acetaminophen‐induced liver injury . NMI is also involved in antiviral response against viral infections . Recently, it is demonstrated that NMI correlates with the severity of inflammation in sepsis patients .…”
Section: Introductionmentioning
confidence: 99%
“…6 NMI is also involved in antiviral response against viral infections. 7 Recently, it is demonstrated that NMI correlates with the severity of inflammation in sepsis patients. 6 The severity of ACLF is also correlated with inflammation, which is contributing to prognosis of ACLF.…”
Section: Introductionmentioning
confidence: 99%